Aristotle’s Ethics as First Philosophy - Baracchi, Claudia (Cambridge University Press, 2013)
By reference to the ethical treatises and the Politics, but also to other texts of the Aristotelian corpus (most notably, the Metaphysics and the treatises of the Organon), the present study undertakes to demonstrate the indissoluble intertwinement of practical and theoretical wisdom (phron¯esis and sophia as well as, concomitantly, praxis and the¯oria) in Aristotle’s thinking. In this manner, I propose that sophia, theoretical wisdom, far from an autonomous and separate pursuit, should be acknowledged as integrally involved in becoming, sensibility, experience, and, hence, action. Of course, this line of inquiry cannot but address critically the established view of the separation, indeed the opposition of the two modes of reason. Such a dichotomous logic is retained even by those who, like Arendt and Gadamer, variously emphasize the practical over against the theoretical and do so by merely inverting the order of the hierarchy.